Paris Olympics: craniofacial and oral traumas - Cicciù, M.; Crimi, S.; Fiorillo, L. (The Journal of Craniofacial Surgery, 2025)
Sports-related traumas are a significant concern in both amateur and professional athletic competitions, often resulting in a variety of injuries, from musculoskeletal damage to craniofacial and dental trauma. These injuries can range from mild abrasions to severe fractures, concussions, or even life-threatening conditions, especially in high-contact sports. Among these, oral and facial injuries are particularly common in sports, such as boxing, football, and gymnastics, where physical impacts to the head and face occur frequently.1 Oral and facial traumas can include dental fractures, avulsions, lacerations to the lips or gums, and more severe injuries, such as mandibular fractures or temporomandibular joint dislocations. Emergency management of these injuries typically involves an initial assessment of the airway, breathing, and circulation (the ABCs of trauma care), followed by hemostasis, pain control, and stabilization of the injured structures. For dental avulsions, immediate replantation is often crucial, while fractures may require immobilization or surgical intervention. The management of facial fractures, especially those involving the maxillofacial skeleton, demands careful coordination between trauma surgeons, maxillofacial specialists, and dentists.